A fault warning for inter-turn short circuit of excitation winding of synchronous generator based on GRU-CNN - Junqing Li; Jing Liu; Yating Chen (Global Energy Interconnection, 2022)
Synchronous generators are important components of power systems and are necessary to maintain its normal and stable operation. To perform the fault diagnosis of mild inter-turn short circuit in the excitation winding of a synchronous generator, a gate recurrent unit-convolutional neural network (GRU-CNN) model whose structural parameters were determined by improved particle swarm optimization (IPSO) is proposed. The outputs of the model are the excitation current and reactive power. The total offset distance, which is the fusion of the offset distance of the excitation current and offset distance of the reactive power, was selected as the fault judgment criterion. The fusion weights of the excitation current and reactive power were determined using the anti-entropy weighting method. The fault-warning threshold and fault- warning ratio were set according to the normal total offset distance, and the fault warning time was set according to the actual situation. The fault-warning time and fault-warning ratio were used to avoid misdiagnosis. The proposed method was verified experimentally.